Natural circulation with DOWTHERM RP and its MARS code implementation for molten salt‐cooled reactors. (19th February 2016) - Shin, Yukyung; Seo, Seok Bin; Kim, In Guk; Bang, In Cheol
Summary: Recently, molten salt has received attention as a promising coolant for advanced nuclear reactors, especially for fluoride salt‐cooled high‐temperature reactor. The heat transfer characteristics of molten salt provide great advantages for application as a primary coolant, because of its superior performance in terms of sustainability, economics, safety, and reliability compared with gas coolant. However, understanding the thermal‐hydraulic characteristics of molten salts by experimental method is difficult because of its high‐temperature corrosion and toxicity issue. Therefore, oil fluids were introduced as simulants for studying the heat transfer phenomena of high Pr (Prandtl number) molten salts. In this study, a scaled‐down experiment using simulant oil was conducted, and scaling laws were applied to investigate a single‐phase natural circulation, which is important in nuclear reactors as a part of their passive safety. DOWTHERM RP (Diaryl Alkyl) was considered as a heat transfer simulant in this study because it matches the relevant dimensionless numbers (Prandtl number, Ra, Grashof number, Reynolds number, etc.) with those of molten salt. Prior to the experiment, the thermophysical properties of both the liquid and vapor phases of DOWTHERM oils were implemented into thermal‐hydraulic system analysis code or multi‐dimensional analysis of reactor safety code, to enable simulation and further study of the molten salts. Then, natural circulation experiments were conducted with the scaled rectangular loop, to establish similarity and experimental feasibility. For the validation, two different codes (multi‐dimensional analysis of reactor safety and computational fluid dynamics (CFD) were used to simulate the same natural circulation loop. From the experimental data, new heat transfer correlation for a single‐phase natural convection was developed, and the existing heat transfer correlations were compared. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This paper presents similarity experiment using simulant oil and scaling laws for molten salt reactor systems. Single‐phase natural circulation with DOWTHERM RP (Diaryl Alkyl) was conducted. For validation, multi‐dimensional analysis of reactor safety code and CFD code were used. Thermophysical properties of DOWTHERM oils were implemented into multi‐dimensional analysis of reactor safety code. From the experimental data, new heat transfer correlation for a single‐phase natural convection was developed, and the existing heat transfer correlations were compared.